Determinants of COVID-19 Severity: A Retrospective Analysis of Clinical and Epidemiological Factors in Durango, Mexico (Epidemiology, Biostatistics, and Public Health, 2025)
Background: The COVID-19 pandemic, caused by SARS-CoV-2, has had a devastating global impact, with millions of confirmed cases and deaths. This study focused on analyzing 63,252 patient records from the state of Durango, Mexico, to identify clinical and epidemiological factors associated with disease severity. Methods: The study employed a descriptive, observational, and retrospective approach, based on open data from the SISVER platform. A descriptive analysis was conducted to summarize demographic and clinical characteristics. A multivariate analysis was performed using the graph of relative inertias to assess how the covariates (comorbidities) were associated with hospitalization, intubation, and death in the patients. Subsequently, odds ratios tests were calculated to evaluate the associations between specific clinical variables, such as pneumonia, obesity, and other comorbidities, and intubation.Results: We were found that the majority of cases (93.8%) were treated on an outpatient basis, while 6.2% required hospitalization. Hypertension, diabetes, and obesity were the most prevalent comorbidities. The mortality rate in the population was 2.1%, particularly in Jurisdiction I, corresponding to the capital city. Pneumonia was strongly associated with intubation (OR = 9.03, 95% CI = 1.0232 – 44.3230, p = 0.03), and obesity also showed an increased risk (OR = 2.64, 95% CI = 1.0021 – 22.4210, p = 0.02). These findings underscore the importance of identifying and managing comorbidities in patients infected with SARS-CoV-2. Conclusion: The results highlight the relevance of social determinants of health and the need for public policies that address inequalities in the context of appropriately managing risk factors to reduce morbidity and mortality associated with COVID-19 in Mexico.
Keywords: COVID-19; comorbidities; morbidity; mortality